Report on Candidates' Work in the Secondary Education Certificate Examinations June 1999: Spanish - Caribbean Examinations Council (CXC, 1999)
This report provides general and detailed comments on the performance of candidates in the June 1999 Caribbean Secondary Education Certificate (CSEC) general and basic proficiency examinations in Spanish.
Keywords: CXC CSEC examinations